Organizational learning and psychological empowerment - Latifian, Ahmad (Opción, 2019)
The purpose of this document is to examine the effect of organizational learning on psychological empowerment with the mediating role of the organizational climate. The research method is the descriptive survey. The main results of the research showed that organizational learning with the mediating role of the organizational climate has a positive effect on the psychological empowerment of employees. In conclusion, when employees participate in decisions and clearly understand their role, they feel self-sufficient and valuable and can influence the contexts of their careers, that is, they believe in their abilities.